TANTANGAN DAN STRATEGI IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI PADA SISWA ATLET PUSAT PENDIDIKAN DAN LATIHAN OLAHRAGA PELAJAR (PPLOP) SMA - Naufal Dzaky Firmansyah; Didi Pramono (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study was motivated by the challenges teachers face in implementing differentiated instruction for student-athletes at the Student Sport and Training Center (PPLOP), who juggle dual roles in academics and athletic performance. The focus of this study is to explore in depth the challenges and strategies teachers use in applying differentiated instruction to student-athletes at PPLOP SMA Negeri 11 Semarang. This study employs a qualitative approach using a case study design. The research subjects consist of four subjects teachers and five student-athletes selected as purposive sampling. Data collection was conducted via interviews, observation, and document analysis. Data analysis utilized source triangulation through interactive model purposed by Miles, Huberman, and Saldana. The findings reveal two main results. First the challenges faced by teachers stem from cultural gaps between curriculum demands and the realities of student-athletes. These gaps manifest in three aspects: planning (student heterogenity, process (physical condition and attendance of student-athletes). Second in response this challenges, teachers developed adaptive strategies in the form of differentiation of content (simplification of material), process (flexibility of learning methods), and products (flexible assigment and examination system). The implementation of differentiation learning of student-athletes requires teachers to be innovators capable of bridging the gap between the ideal curriculum requirements and the realities of the ground. Sucsessful implementation will be achieved if systemic support in the form of flexible policies and collaboration among various stakeholders can be implemented simultaneously.